Corporate social responsibility and service quality provision in shipping firms: financial synergies or trade-offs?. Issue 1 (2nd January 2017) - Yuen, Kum Fai; Thai, Vinh V.
ABSTRACT: This study examines whether the implementation of corporate social responsibility (CSR) and provision of service quality (SQ) to satisfy shippers result in financial synergies or trade-offs for shipping firms. To address this question, a contingency framework was introduced in this study. The literature was first reviewed for hypotheses development, followed by interviews with eight industry practitioners. Subsequently, an internet survey was administered to 156 shipping firms in Singapore, and the obtained data were analysed using path model analysis and simple slope analysis. The results indicate that CSR complements SQ and provides additional but modest financial contribution to shipping firms via customer satisfaction. In addition, synergistic interactions between SQ and CSR were found. Although there are financial synergies from the implementation of CSR and provision of SQ, the analysis reveals that CSR should only be engaged when a shipping firm is fairly competent at delivering quality shipping services. This paper contributes to both theory and practice by framing business decisions on implementing CSR under contingency theory and offering a strategic approach to managing SQ as well as CSR of shipping firms.